Color-sensitive ultrafast optical modulation and switching of terahertz plasmonic devices - Kumar, Abhishek (2019)
2D micro‐nanostructured metal films with hole arrays show promising features such as the extraordinary transmission of light. Such systems are interesting in the field of subwavelength photonics and nonlinear optics due to their high field confinement in addition to their inherent spectral scalability and frequency selective response. Several active schemes to control the extraordinary transmission are recently demonstrated. However, these dynamic devices do not reveal any obvious color‐dependent modulation of the resonant transmission behavior. Here, color‐sensitive ultrafast modulation of extraordinary resonant transmission of terahertz (THz) waves through 2D metallic hole arrays is demonstrated. Pumping the silicon beneath the metallic array with light of different colors and identical fluences exhibit significantly different ultrafast switching dynamics and modulation. The color‐dependent sensitivity and control of THz waves at an ultrafast timescale provide an extra degree of freedom that opens up new opportunities for future applications in active subwavelength optics, optoelectronics, and all‐optical switching of THz photonic devices.